2020
DOI: 10.1186/s12884-020-03313-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and socioeconomic gradient in low birth weight in Ethiopia: further analysis of the 2016 demographic and health survey data

Abstract: Background Evidence suggests appearance of socioeconomic gradient in the probability of low birth weight (LBW). Such evidence, however, is scanty in Ethiopia. The study aimed to examine the prevalence of and socioeconomic gradient in LBW in Ethiopia. Method Data for the study were drawn from the Ethiopia Demographic and Health Survey conducted in 2016. The 2016 EDHS is the fourth wave in the series of nationally representative household surveys carried out in the country to deliver up-to-date health and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
3
4
1
Order By: Relevance
“…The proportion of babies born with LBW (7.5% (95% CI 4.8% to 11.0%)) was comparable with the findings from the nationwide study using the 2016 Ethiopia Demographic Health Survey data, which was 13.2% (95% CI 10.7% to 15.7%), 38 but lower than a finding from a metaanalysis conducted in 2018 in Ethiopia (pooled LBW data from 1995 to 2017), which was 17.3% (95% CI 14.1% to 20.4%). 39 Studies conducted in different parts of the country reported that maternal education, 38 employment status, income and maternal age 39 are significantly associated with a baby's birth weight. However, these factors were not significantly associated with birth weight in our study.…”
Section: Discussionsupporting
confidence: 77%
“…The proportion of babies born with LBW (7.5% (95% CI 4.8% to 11.0%)) was comparable with the findings from the nationwide study using the 2016 Ethiopia Demographic Health Survey data, which was 13.2% (95% CI 10.7% to 15.7%), 38 but lower than a finding from a metaanalysis conducted in 2018 in Ethiopia (pooled LBW data from 1995 to 2017), which was 17.3% (95% CI 14.1% to 20.4%). 39 Studies conducted in different parts of the country reported that maternal education, 38 employment status, income and maternal age 39 are significantly associated with a baby's birth weight. However, these factors were not significantly associated with birth weight in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, this study revealed that women in all wealth status categories, compared to the wealthiest, had a higher probability of giving birth to LBW babies. An earlier study analyzing secondary data from the 2016 Ethiopia Demographic and Health Survey in Ethiopia also reported similar results with the incidence of LBW being dominant among the poor [ 44 ]. Poor households have limitations in providing food for all family members, including pregnant women.…”
Section: Discussionsupporting
confidence: 53%
“…According to previous research [ 1 , 15 , 16 ], Ethiopia is one of the countries with the most significant number of low birth weight babies globally. Furthermore, while the prevalence of low birth weight has decreased in the country from time to time, more work is needed to promote this decline and to limit the detrimental implications of the occurrence [ 1 , 4 , 13 , 25 ]. In this study, the average birth weight was 3268.983 g, with a maximum of 6000 g and a minimum of 500 g, while quartiles one and three were 3000 and 3750 g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, identifying significant features associated with LBW is an essential initial step. An assessment of the literature [4,22] and data availability is used to do this. These 25 features are shown in Table 1 below.…”
Section: Preprocessing Of Datamentioning
confidence: 99%
See 1 more Smart Citation